Analisis Faktor Fundamental dan Laba Akuntansi terhadap Harga Saham pada Sub Sektor Lembaga Pembiayaan di BEI - Amilia Paramita Sari (Universitas Batanghari, 2018)
The aims of this research was to investigate of fundamental factor and accounting profit could be considered as drivers of stock price. This research used method of purposive sampling. The population in this research was 17bcompanies and the samples in this research were 7 financial companies in Indonesia Stock Exchange in 2012-2016. While the analysis instrument in this research was multiple linear regression. The simultaneous regression testing (F-test) indicated that the variable of Price Earning Ratio (PER), Earning Per Share (EPS), Book Value (BV) and accounting profit (LAK) had significant influence to the stock price. In the partial regression testing (t-test), the variable of Price Earning Ratio (PER), Book Value (BV) and accounting profit (LAK) had siginificant influence to the stock price. Meanwhile, the Earning PerShare (EPS) variable did not have siginificant influence to the stock price. The result of this research showed that stock price was influenced by the interaction between fundamental factor and accounting profit from investment.Keywords: Price Earning Ratio (PER), Earning Per Share (EPS), Book Value (BV), accounting profit, stock price